Integrated studies of the Early Iron Age centres between the south-eastern Alps and the Pannonian plain - Mušič, Branko; Črešnar, Matija; Potrebica, Hrvoje (2013)
The Early Iron Age landscapes between the south-eastern Alps and the Pannonian plain are marked by monumental structures such as hillforts with adjacent barrow cemeteries. Some of them are probably just central places of much more complex landscapes which also include lowland sites located in the central parts of the river plains and many other features. The use of remote sensing in recent years immensely improved and our knowledge of these sites and even more of complex landscapes which surround them. New approach in our research projects which included application of aerial imagery, lidar scanning and geophysics, often combined in integrated studies, for the first time covered larger areas around known sites, and at the same time enabled detailed and multilayered approach in detailed study of particular sites. This time we will present application of several geophysical methods with an accent on some non-traditional interpreting tools like direct and inverse problem of interpretation. We will also present other advanced processing flows with aim to establish specific prehistoric targets in different natural settings and archaeological contexts. The special attention was given to innovative, case sensitive approach to structural analysis of late prehistoric barrows.